Challenges and Dynamics of Governance Law Implementation: A Critical Perspective In The Contemporary Context - Yanto, M.; Royani , Ahmad; Nahdliyah , Hadziqotun; Paramartha, Meris Sabrina (Jurnal Independent, 2024)
Abstract The implementation of government law in the contemporary context poses complex challenges and changing dynamics. This article outlines the diverse aspects that influence the effectiveness of governmental legal systems, as well as presents a critical perspective on addressing these challenges. Political polarization, technological advancements, and global interconnection are major factors influencing the implementation of government laws. High political polarity can hinder effective policymaking and law enforcement processes, while technological advances, such as the internet and social media, bring new challenges in regulating the behavior of people and private entities. Global interconnection complicates the implementation of governing laws because events in one country can have far-reaching repercussions in another, requiring strong international cooperation in law enforcement. Inequality of access to the justice system, high litigation costs, and lack of legal information are also obstacles to obtaining justice. Some individuals may struggle to access adequate legal aid or face financial difficulties in bearing the costs of litigation. In addition, a lack of understanding of their rights or due process can make it difficult for individuals to fight for their rights in the justice system. To address these challenges and dynamics, comprehensive strategic measures are needed, including strengthening government legal institutions, increasing transparency and accountability, using technology in law enforcement, strengthening international cooperation, and community empowerment. Thus, it is expected that the implementation of government law can be more effective and responsive to the needs of society in the complex contemporary era.